Differences in electromyographic activity of biceps brachii and brachioradialis while performing three variants of curl - Marcolin, Giuseppe (PeerJ, 2018)
BACKGROUND: Dumbbell curl (DC) and barbell curl in its two variants, straight (BC) or undulated bar (EZ) are typical exercises to train the elbow flexors. The aim of the study was to verify if the execution of these three variants could induce a selective electromyographic (EMG) activity of the biceps brachii (BB) and brachioradialis (BR). METHODS: Twelve participants performed one set of ten repetitions at 65% of their 1-RM for each variant of curl. Pre-gelled electrodes were applied with an inter-electrode distance of 24 mm on BB and BR. An electrical goniometer was synchronously recorded with EMG signals to determine the concentric and eccentric phases of each variant of curl. RESULTS: We detected higher activation profile of both BB (P < 0.05) and BR (P < 0.01) during the EZ compared to the DC. Higher levels of activation was found during the concentric phase for only the BR performed with an EZ compared to DC (P < 0.001) and performing BC compared to DC (P < 0.05). The eccentric phase showed a higher activation of the BB muscle in EZ compared to DC (P < 0.01) and in BC compared to DC (P < 0.05). The BR muscle showed a higher activation performing EZ compared to DC (P < 0.01). DISCUSSION: The EZ variant may be preferred over the DC variant as it enhances BB and BR EMG activity during the whole range of motion and only in the eccentric phase. The small difference between BC and EZ variants of the BB and BR EMG activity makes the choice between these two exercises a matter of subjective comfort.